Respuesta :
Answer:
Option (d) is correct.
(1, 0) is the solution of the given system of equation.
Step-by-step explanation:
Consider the given system of equation
4x - 2y = 4 ........(1)
6x - 4y = 6 ........(2)
We have to solve the system algebraically ,
We will solve it by elimination method,
Multiply equation (1) by 2, we get,
(1) ⇒ 8x - 4y = 8 ............(3)
Subtract equation (2) from (3) , we get,
8x - 4y - (6x - 4y) = 8 - 6
8x - 4y - 6x + 4y = 2
8x - 6x = 2
⇒ x = 1
Substitute x = 1 in (1) and solve for y , we get,
⇒ 4x - 2y = 4 ⇒ 4 (1) - 2y = 4 ⇒ 2y = 4 - 4 ⇒ 2y = 0 ⇒ y = 0
Thus, (1, 0) is the solution of the given system of equation.
Option (d) is correct.
Answer:
Choice d is correct answer.
Step-by-step explanation:
We have given a system of equations.
4x-2y = 4 eq(1)
6x-4y = 6 eq(2)
We have to solve it for x and y.
We use method of elimination to solve this system.
Multiplying by 2 to both sides of eq(1), we have
2(4x-2y) = 2(4)
8x-4y = 8 eq(3)
Subtracting eq(3) to eq(2), we have
8x-4y-(6x-4y) = 8-6
8x-4y-6x+4y = 2
2x = 2
Dividing by 2 to both sides of qbove equation , we have
2x/2 = 2/2
x = 1
Putting the value of x in eq(1), we have
4(1)-2y = 4
4-2y = 4
Adding -4 to both sides of above equation , we have
-2y = 0
Dividing by -2 to both sides of above equation, we have
y = 0
Hence, the solution of given system is (1,0).